(In)visible materialities in the context of dementia care. Issue 1 (27th September 2019) - Cleeve, Helena; Borell, Lena; Rosenberg, Lena
Abstract: Seemingly mundane materialities are intertwined with important, but often neglected, care interactions. It has been argued that if healthcare professionals paid more attention to the roles materialities can have, everyday routines could become important occasions for care. In response to such proposals, we argue that it is relevant to examine how materialities are currently understood. In this article, we explore materialities as part of work in a dementia unit. Using abstracted illustrations of everyday materialities to elicit reflections, we conducted 11 individual interviews with certified nursing assistants. Through phenomenographic analysis we explain our findings as three different categories conceptualising understandings of materialities as: 'tools for care', 'a set of principles for care' and 'caring relationships'. Our analysis indicates that understanding materialities as instruments was reinforced and made visible through the healthcare organisation while understanding materialities as part of specific relationships with residents appeared informal and less visible. How materialities were understood seemed to have several implications for residents. While care practices could benefit from nursing assistants' abilities to alternate between ways of understanding materialitites, such competence seemed dependent on how professional care was organised, structured and materialised.